Ethical assumptions and ambiguities in the Americans... - Kopelman, Loretta M. (Journal of Medicine & Philosophy)
Examines the effectiveness of the Americans With Disabilities Act (ADA) in protecting disabled persons from discrimination and prejudice. What year act was passed into law; Advantages and disadvantages of ADA; How persons will qualify for protection under the ADA; Types of restrictions placed on persons who qualify; Analysis of act.